Nanoparticle elasticity directs tumor uptake - Peng Guo (Nature Portfolio, 2018)
Nanoparticle elasticity is thought to play an important role in drug delivery, but is little studied. Here, the authors use nanolipogels with tunable moduli to study the effect of particle elasticity on in vitro cellular uptake and in vivo tumor uptake, finding that stiffer particles are not as easily internalized.